PENGARUH THORACIC SPINE MOBILITY EXERCISE DAN CORE STABILITY EXERCISE TERHADAP POSTUR PADA IBU HAMIL - Achirda, Nur; Jannah, Roikhatul (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Background: Kyphosis is a change in the position of the spine which causes the surface of the back to bend less than normal, especially in pregnant women. (Mclester, J. and Pierre, S.P., 2008). Changes in spinal posture and an increase in abdominal diameter and sagittal diameter which shift the center of mass of the body to the anterior cause lower back load and pressure on the lower back, resulting in lower back pain felt during pregnancy. The lower back, namely the lumbar during pregnancy becomes lordosis and the thoracic becomes Kyphosis. Vertical balance has decreased. These changes in posture are experienced by pregnant women (Betsch, 2015). Changes in posture in pregnant women during pregnancy can cause lower back pain (Michoński, 2016). The correct way to treat Kyphosis is by doing exercises. Spinal mobility exercises Thoracic Spine Mobiliy Exercise is one that aims to improve the Kyphosis angle after exercise and corrects it significantly. Research by Nicola R et al (2020) showed that good muscle stability can reduce the risk of injury and can improve the Kyphosis angle after training and correct it significantly compared to before training, so that it can produce dynamic and strong dynamics. Apart from the Thoracic Spine Mobility Exercise, Core Stability Exercise can also be given for Kyphosis disorders, because it can make the core muscles work in harmony with complex contractions, so that dozens of muscles in the spine, trunk and surrounding areas will stabilize and reach a neutral position. during body movements and maintains a stable position in the vertebrae (the neutral zone). Core Stability Exercise also aims to improve the Kyphosis angle after exercise and corrects it significantly compared to before exercise. Method: This research is Pre-Experimental with a One Group Pre Test and Post Test design. Objective: This study was to determine the effect of providing Thoracic Spine Mobility Exercise and Core Stability Exercise interventions on Kyphosis Posture in Pregnant Women with a total of 23 respondents. Thoracic Spine Mobility Exercise and Core stability exercise interventions were given for 4 weeks, three times per week. Results and Discussion: The results of the Shapiro-Wilk normality test showed a p value >0.05 in each group of normally distributed data. The results of hypothesis testing after providing intervention in the form of Thoracic Spine Mobility Exercise and Core Stability Exercise, there was a significant difference, namely 0.00 (<0.05). Conclusion: After being given intervention from 23 respondents whose Kyphosis, 17 respondents became normal and 6 respondents started to improve, it was concluded that there was a significant effect on posture correction in Kyphosis patients after being given the Thoracic Spine Mobility Exercise and Core Stability Exercise intervention in pregnant women.